AAV‐mediated gene therapy as a strategy to fight obesity and metabolic diseases. Issue 8 (18th July 2018) - Sponton, Carlos Henrique; Kajimura, Shingo
Abstract : The fibroblast growth factor 21 (FGF21) is a member of the FGF superfamily that now comprises 22 members identified in humans. Unlike the canonical role of most FGF family members, FGF21 is released into the circulation and acts as an endocrine hormone by binding with low affinity to FGF receptors (FGFRs) as well as to the co‐receptor β‐klotho in the target cells to trigger the ERK1/2 and MAPKs signaling pathways. Described initially as a hepatokine, subsequent studies identified significant amounts of FGF21 transcript in the pancreas, the adipose tissue, and the skeletal muscle. FGF21 expression is highly regulated by environmental stimuli such as starvation, ketogenic diet, cold exposure, and exercise. Abstract : In this News & Views article, Kajimura and Sponton discuss the advantages and therapeutic benefits of considering FGF21 gene therapy against obesity and metabolic disorders.